The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/aec.12663
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cattle grazing regimes on tropical savanna bird assemblages

Abstract: Globally, agricultural land use is implicated in the decline of avifauna. In rangelands (areas used for livestock grazing), bird community responses to grazing can be complex, species-specific and scale dependent. A greater understanding of bird responses to grazing will lead to more meaningful management recommendations. We tested the hypothesis that foraging height predicts bird species' responses to grazing, such that species using lower vegetation strata are most likely to respond to the impacts of livesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 55 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…The effects of livestock grazing on bird assemblages are highly variable (Davies et al . 2010, Neilly and Schwarzkopf 2019), partly because the effects of grazing livestock on ecosystems vary with the type of herbivore (Sankaran et al 2008). Moreover, livestock grazing effects are difficult to assess due to scarcity of areas without livestock grazing (Bellis and Muriel 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of livestock grazing on bird assemblages are highly variable (Davies et al . 2010, Neilly and Schwarzkopf 2019), partly because the effects of grazing livestock on ecosystems vary with the type of herbivore (Sankaran et al 2008). Moreover, livestock grazing effects are difficult to assess due to scarcity of areas without livestock grazing (Bellis and Muriel 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, Köhler et al (2016) and Kerekes & Végvári (2016) found that associations between bird abundance and grazing intensity varies greatly among bird species. Also Neilly & Schwarzkopf (2019) described that responses of birds to grazing are often complex and will reflect habitat requirements of the individual bird species. Whether a possible effect of natural grazing in a nature reserve is meeting conservation goals thus depends on which species one aims to protect.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of grassland to forestry further threatens birds reliant on open anthropogenic habitat (Mortelliti & Lindenmayer 2015). Groundnesting species are particularly sensitive to high grazing pressure from livestock, whereas groundforagers are less sensitive (Baker-Gabb et al 2016, Neilly & Schwarzkopf 2019.…”
Section: Australasia (74 Studies)mentioning
confidence: 99%
“…Many Australasian grasslands, including 95% of Australia's Northern Plains (Department of Sustainability and Environment 2010), have been lost or degraded by conversion for livestock pastures and cropping, impacting a range of grassland birds including the Plains‐wanderer Pedionomus torquatus (Baker‐Gabb et al . 2016, Neilly & Schwarzkopf 2019) and Golden‐shouldered Parrot Psephotellus chrysopterygius (Crowley & Garnett 1998). Conversion of grassland to forestry further threatens birds reliant on open anthropogenic habitat (Mortelliti & Lindenmayer 2015).…”
Section: Regional Summariesmentioning
confidence: 99%